Pengaruh Penggunaan Media WAFEL (Wayang Flanel) Terhadap Kemampuan Menyimak Siswa Kelas II SDN Cikupa - Rachmah, Elsa Siti; Suryaman, Oman (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study was to determine how the influence of Wayang Flannel media (WAFFLES) on the ability to listen to stories of Cikupa State Elementary School students before and after the application of flannel puppet media (Waffles). This research method is quantitative, this type of research is Quasi Experiment with Nonequivalent Control Design. Sampling in this study used probability sampling techniques. This study involved 59 students, grade II of Cikupa State Elementary School. The sample studied was 59 students of grades IIA and IIB. Data collection was carried out with initial and final tests of six questions, observation, interviews, and documentation. Data were analyzed descriptively quantitatively. The results of the study showed that WAFEL (Wayang Flannel) media can improve students' listening skills if given WAFEL (Wayang Flannel) media entitled ants and grasshoppers. From the results of the hypothesis test with the testing criteria if the value of Sig. (2-tailed) <0.05, then Ho is rejected and Ha is accepted with a significance level = 0.05, obtained a value of 0.005 so it can be concluded that Ho can be rejected and Ha is accepted, and the level of effectiveness is proven by the n-gain score test of 66.57 which is included in the criteria for being quite effective. This shows that WAFFLE media affects students' listening skills.